The origins of worker mobilisation Australia 1788-1850 - Quinlan, Michael 1951- (Routledge, 2018)
Reconsidering the collective impulse and the colonial context -- Law, the courts and inequality at work -- Overview of worker organisation, 1788-1850 -- Analysing the components of organisation -- Organisation in transport and maritime activities -- Organisation in the rural and extractives sectors -- Organisation in construction and building materials -- Organisation in manufacturing and related trades -- Organisation in government and community services -- Organisation in commercial, personal services and retailing -- Peak and political organisation -- Re-evaluating worker mobilisation -- Index
Includes index
Keywords: Geschichte 1788-1850; Arbeiterbewegung; Gewerkschaftsbewegung; Australien; 1788-1850